2012
DOI: 10.1089/ten.tec.2011.0579
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Structural Integrity and Extracellular Matrix Components of Tracheal Allografts Following Cyclical Decellularization Techniques: Comparison of Three Protocols

Abstract: Tracheal reconstruction is indicated in cases of malignancy, traumatic injury, and subglottic or tracheal stenosis. Recent progress in airway transplantation has provided renewed optimism for potential solutions for defects involving more than half of the tracheal length in adults or one-third of the tracheal length in children. Biologic scaffolds derived from decellularized tissues and organs have shown great promise in tracheal allotransplantation, and cyclical decellularization techniques have been hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 22 publications
4
77
0
1
Order By: Relevance
“…With respect to trachea and lung, a number of recent publications have comparatively assessed different de-cellularization protocols. Notably, the resulting architecture and extracellular matrix (ECM) protein composition of either trachea or lungs may differ substantially between the different regimens utilized [57]. Whether this will subsequently affect re-cellularization of scaffolds and therefore the generation of functional tissue suitable for transplantation, remains unresolved [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to trachea and lung, a number of recent publications have comparatively assessed different de-cellularization protocols. Notably, the resulting architecture and extracellular matrix (ECM) protein composition of either trachea or lungs may differ substantially between the different regimens utilized [57]. Whether this will subsequently affect re-cellularization of scaffolds and therefore the generation of functional tissue suitable for transplantation, remains unresolved [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the consideration of the long-term therapeutic application of scaffold-based strategies, several limitations become apparent. First, previous studies indicate that, even in the setting of grossly preserved structure and extracellular components, the decellularized lung scaffold demonstrates a large amount of "leakiness" that may at least partially reflect damage sustained during the decellularization procedure (12,23). Second, other studies demonstrate that the decellularization process can negatively impact ECM protein integrity (1,31), which may impede its ability to support infused progenitor cells or to persist long term in vivo.…”
mentioning
confidence: 99%
“…This mechanical detergent-enzymatic protocol requires solely one cycle. Haykal et al, 25 conducted a comprehensive comparative study between the protocols and concluded that the 17cycle protocol caused a significant decrease in mucosal and cartilaginous components of the native trachea. In addition, the first and second protocols appear to cause an increase in compliance, thereby reducing the reliability on longterm maintenance of graft integrity, while tracheae treated with the third protocol, appeared more comparable to the native trachea.…”
Section: Matricesmentioning
confidence: 99%